Physical and mental status at 4 years of age of survivors of the respiratory distress syndrome. Follow-up report from the collaborative study - Fisch, R O; Bilek, M K; Miller, L D; Engel, R R (The Journal of pediatrics, 1975)
Fifty-eight survivors of the respiratory distress syndrome were evaluated at age 4 years for deficits in neuromotor performance and physical growth in a prospective study. Comparisons between RDS survivors and 290 matched controls plus 35,198 unmatched controls demonstrated that for each group the neuromotor performance was adversely affected by either low birth weight or low socioeconomic standing. Except for infants with birth weights above 2.5 kg, the RDS survivors performed as well as the two control groups. Comparisons with siblings failed to reveal a decrement in the RDS survivors. Hypothyroidism was more frequent among the RDS survivors than among the control subjects in the highest category of birth weight.